Towards the development of electrospun mats from poly(ε-caprolactone)/poly(ester amide)s miscible blends - Lamas, Miguel (2018)
In this work, electrospun mats made from miscible poly(ε-caprolactone) (PCL)/poly(ester amide) (PEA) blends were prepared, for the first time. The well-known immiscibility issues between these two type of polymers were overcome through the synthesis of a novel tailor-made compatibilizer blocky PEA, comprising well defined PCL and PEA8L6 blocks (PCL-PEA8L6). The PCL-PEA8L6 was synthesized for the first time in this work and was characterized in terms of its chemical structure and thermal properties. Regarding the mats, it was found that their properties (morphology, porosity, wettability, thermomechanical) can be easily adjusted by the ratio of the components of the mixture to be electrospun. Increasing amounts of PEA led to more hydrophilic mats, with enhanced in vitro degradability, both hydrolytic and enzymatic. The in vitro cytotoxicity tests carried out with normal human dermal fibroblasts (NHDF) revealed that the samples do not elicit any acute adverse effect on the cells. Moreover, the NHDF were able to grow and proliferate in the surface of the electrospun mats. The data presented in this contribution is a proof-of-concept that can be used to address immiscibility issues between different types of polymers broadly used in biomedical applications.